Exploring the interplay between posttraumatic stress disorder, gut microbiota, and inflammatory biomarkers: a comprehensive meta-analysis - Petakh, Pavlo; Oksenych, Valentyn; Kamyshna, Iryna; Boisak, Iryna; Lyubomirskaya, Katerina; Kamyshnyi, Oleksandr (Frontiers in Immunology, 2024)
Posttraumatic stress disorder (PTSD) is a pervasive mental health condition stemming from exposure to trauma, particularly relevant in the context of current global conflicts. This meta-analysis delves into the intricate relationship between PTSD, gut microbiota, and inflammatory biomarkers. Fifteen studies were systematically reviewed, with nine examining inflammatory markers and six exploring gut microbiota composition. Despite significant heterogeneity, no discernible differences in inflammatory biomarkers were observed between the PTSD and control groups. Also, studies of the gut microbiota showed mixed results, with differences in alpha diversity and certain taxa. This showed how complicated the microbiota-gut-brain axis is in PTSD. The synthesis of these results offers insights into potential therapeutic avenues and emphasizes the need for further research to unravel the underlying mechanisms.